PENDAMPINGAN KELOMPOK TANI DALAM PEMANFAATAN LIMBAH KULIT MANGGIS MENJADI PRODUK OLAHAN - Sulaeni, Sulaeni; Sumantri, Ari Tresna (Jurnal Pengabdian Dinamika, 2019)
Mangosteen (Garcinia Mangostana L.) is a tropical fruit commodity that has the potential to bedeveloped as a support for popular economy. The mangosteen peel waste can be processed intofood products, medicines, and cosmetics. Using mangosteen peel into processed products canincrease the income of mangosteen farmers and reduce mangosteen peel waste which can pollutethe environment while harvesting mangosteen. This assistance aims to increase the knowledge ofmangosteen farmers by processing and utilizing mangosteen peel waste into processed foodproducts, as well as being a source of income and new business for farmers and the surroundingcommunity. The method used in mentoring mangosteen farmers is the Coundeling, FGD, anddistributing questionnaires. The location of assistance in two farmer groups is the Mekar RahayuFarmer Group and the Barokah Farmer Group in the Bojong District, Pandeglang Regency. Thetiming of the assistance activities was carried out in June 2019. The target groups weremangosteen farmers who were members of farmer groups. The result of this assistance is toincrease farmers 'knowledge to utilize leather waste into processed products that can increasefarmers' income, and can be used as a new source of income for the community.